Investigation of energy dissipation and flow regime over various forms of stepped spillways. (28th November 2016) - Mero, Shimal; Mitchell, Steve
Abstract: The efficient operation of reservoirs relies on the effective release of water during flooding, requiring a good understanding of spillways and their hydraulics. A series of experiments was conducted in a laboratory flume on a stepped spillway model with moderate slope (26.6°) for discharges up to 0.0121 m 3 /s. Using regular uniform horizontal steps of 5 cm height, then several new step configurations including inclined and horizontal curved steps with and without reflector blocks, the flow patterns were investigated. The energy losses over a horizontal stepped spillway were compared with those obtained in a number of similar, previous studies, and with the results obtained for the new step configurations. Good agreement was shown with previous results for horizontal steps, and the inclined and horizontal curved steps dissipated about twice as much energy as the horizontal steps. The results highlight the importance of considering a variety of step forms in spillway design where flows are unpredictable and energy dissipation is important.